The Impact of a One-Year Teacher Training Programme in Uganda - Habib Kato; Lawrence Eron; John Maani; Aron Y. Otto; Daniel Okot; Santo Auma-Okumo; Sarah Bunoti; Andrew Cula (Flexible Learning Association of New Zealand, 2012)
Education for all, life-long learning, and other associated developments are placing great pressure on Uganda to provide enhanced access for education to its schoolage and adult populations. This requires innovation in the provision of education. Distance education (DE) is expanding rapidly, especially in the training of teachers. However there are limited numbers of experienced and qualified practitioners to deliver and manage such innovative distance education initiatives. Kyambogo University, Uganda, in collaboration with the International Extension College (IEC) of the United Kingdom, designed a one-year study programme on introductory aspects of distance education delivery and management, and availed this to selected groups of inexperienced and unqualified practitioners of the DE mode of delivery. This study programme was delivered by the distance mode. A research exercise was undertaken to assess the impact of this one-year study programme on the participants: on their understanding of DE issues and on the nature of their continuing work in supporting, delivering, and managing DE. This article discusses the main findings from the research and the clearly positive impact that such an applied study programme has had-most importantly on sensitizing participants to the unique cultural needs and study contexts of the distance learner.